THE EFFECT OF AN EDUCATIONAL PROGRAM ACCORDING TO THE SHAMAK MODEL IN DEVELOPING STUDENTS' COGNITIVE ACHIEVEMENT AND OFFENSIVE HANDBALL SKILLS - Majid Mohammed Msaed; Ihsan Ali Thabit (Journals Park Publishing, 2022)
The use of modern educational technologies exemplified by the Schimek model is one of the modern models in learning, which works to stimulate the senses of the learner, which is reflected in the skill performance well, and through which the scientific content can be presented in a clear and straightforward manner, which may contribute to the development of the learner's abilities and skills and thus increase his cognitive achievement. In an effort to impact the cognitive achievement of the most essential individual defensive skills in handball, it is crucial to conduct research based on the development of a curriculum in accordance with the Shamak model's techniques. Students and through the experience of the researchers of the game of handball and its follow-up to most educational units, and because we have experience in this field as teachers of this subject, they discovered that most curricula do not carry with them important strategies for processing information, and this is what causes weakness in learning some aspects of knowledge and offensive and defensive skills, especially individual, which affects On the difficulty of employing these individuals. As a result, it impacts the learner's degree and learning tendencies, so researchers turned to a curriculum based on the Shamak model in cognitive achievement to address this issue.
Keywords: Educational Program, Shamak Model Cognitive Achievement, Offensive Handball.